Answer:
x = 8, or -11.
Explanation:
Given:
the given expression.
![2x^2+6x-14=0](https://img.qammunity.org/2021/formulas/mathematics/middle-school/knbg4vz6zcf2phr7fa8xu60ecrvmie0xpw.png)
We need to solve the given expression by completing the square.
Solution:
Rewrite the expression as:
![2x^2+6x-14=0](https://img.qammunity.org/2021/formulas/mathematics/middle-school/knbg4vz6zcf2phr7fa8xu60ecrvmie0xpw.png)
Whole expression divided by 2.
![x^2+3x-7=0](https://img.qammunity.org/2021/formulas/mathematics/middle-school/umozcx1en3qglzbdlz6luxpqjq5aa9skx5.png)
Where:
![b=3\ and\ c=-7](https://img.qammunity.org/2021/formulas/mathematics/middle-school/irrlufveqwnyzhagnvg1o0lm0hdgs3f4f2.png)
Solve the given expression by the following formula.
--------------(1)
Substitute b and c value in equation 1.
![(x+(3)/(2))^2-((3)/(2))+(-7)=0](https://img.qammunity.org/2021/formulas/mathematics/middle-school/3eyv7jxy8s1wfpo4k2wjq69aygy2ub2r7d.png)
![(x+(3)/(2))^2-(3)/(2)-7=0](https://img.qammunity.org/2021/formulas/mathematics/middle-school/ylc4ky81x5lgtih1i7ucfkdklqubwsd1a8.png)
![(x+(3)/(2))^2+(-3-7* 2)/(2)=0](https://img.qammunity.org/2021/formulas/mathematics/middle-school/luan117jntwspfv8c2sdgfuery3i3nqaq7.png)
![(x+(3)/(2))^2+(-3-14)/(2)=0](https://img.qammunity.org/2021/formulas/mathematics/middle-school/wpngo09dljdzf74v68nr2z3pv7kvtz5eq2.png)
![(x+(3)/(2))^2+(-19)/(2)=0](https://img.qammunity.org/2021/formulas/mathematics/middle-school/hkmg33j7cja0iatuqwpe0gpuucuvqnjr09.png)
![(x+(3)/(2))^2-(19)/(2)=0](https://img.qammunity.org/2021/formulas/mathematics/middle-school/ccx99vc5c2mohcusjlxhtbuup552jdz1f5.png)
Add
both side of the equation.
![(x+(3)/(2))^2-(19)/(2)+(19)/(2)=(19)/(2)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/zxhyvspc4e8wl6chuqozdp7w7719x6tqxg.png)
![(x+(3)/(2))^2=(19)/(2)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/7xkmktred00gny43eylwuyjl2zhvbyed60.png)
Square root of the whole equation.
![\sqrt{(x+(3)/(2))^2}=\sqrt{(19)/(2)}](https://img.qammunity.org/2021/formulas/mathematics/middle-school/vswnx5aozgjra4omi68af9fdpgz7ro6p7j.png)
--------(1)
For positive sign.
Add
both side of the equation 1.
![x+(3)/(2)-(3)/(2)=(19)/(2)-(3)/(2)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/vzrxpez06vnonrjj671y1pldql3x6jclrn.png)
![x=(19)/(2)-(3)/(2)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/z3dq4x623avezd12mrrpqi07zame2shl17.png)
![x=(19-3)/(2)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/8hy24wkmpuxxuotyr2oilf9ykx2yg8gaot.png)
![x=(16)/(2)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/e48q5zh339237unbgzlxe9bb23eicl6b6b.png)
x = 8
Similarly for negative sign.
x = -11
Therefore, the value of x = 8, or -11.